Cell culture developing and the imaging of total protein product changing with SDS-PAGE in Saccharomyces cerevisiae - Aslan, Abdullah (Mattioli 1885, 2018)
Five groups were created in this work. i:Control group, ii: H2O2 group, iii: H2O2 + % 10 Mulberry Juice (MBJ) group, iv: H2O2 + % 15 MBJ, v: H2O2 + % 25 MBJ group. After sterilization, H2O2 and fruit juice were inserted different concentration to Saccharomyces cerevisiae (S. cerevisiae) cultures and the cultures were developed at 30 degrees C for 1h, 3h, 5h and 24 hours (overnight). S. cerevisiae cell growth was computed by spectrophotometer, total protein alteration was analysed by SDS-PAGE electrophoresis and reckoned with bradford method. our studies results indicated that; cell developing increased in MBJ groups in proportion to the positive control (H2O2) group at different growing times (1, 3, 5 and 24 hours) (p<0,05). As a result MBJ has a preservative role for reduce the oxidative damage and expanded cell developing and encourage protein synthesis in S. cerevisiae.
Keywords: S. cerevisiae; mulberry juice; hidrogen peroxide; protein expression; SDS-PAGE